Green Synthesis of ZnO Oxide Nanoparticles using Acorus Calamus Leaf Extract: Effect of Solution pH - Aina Nabila Rosli; Nurul Aisyatul Alissa Mohd Agos; Abu Bakar Sidik, Dilaeleyana; Nur Hanis Hayati Hairom (Multidisciplinary Applied Research and Innovation, 2024)
The green synthesis of zinc oxide nanoparticles (ZnO NPs) is cost- effective, biocompatible, easy and upscale-able. The method gaining attention due to their environmentally friendly applications which use renewable resources. Acorus calamus leaf extract has been used for various purposes, including medicine. This study synthesized ZnO NPs using a greener process using precipitation method under different pH levels. The resulting ZnO NPs were characterized using Fourier Transform Infrared (FTIR), and X-Ray Diffraction (XRD). The results show the existence of spherical, hexagonal wurtzite structures in the synthetic ZnO NPs. Next, Fourier Transform Infrared (FT-IR) analysis was performed to identify the functional groups in ZnO NPs. It shows the difference between pH5, pH 6, pH 7 and pH 8. The more acidic the solution, the sharper the peak of the functional group (C-H) shown. The study found that changing pH affects the activity of the solution, potentially making it useful in medicine.